LA RÉPUBLIQUE POPULAIRE ET DÉMOCRATIQUE DE CORÉE (RPDC) FACE À LA RECONFIGURATION DES RAPPORTS DE FORCES INTERNATIONAUX - Elzein, Derek (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2018)
This paper aims to reflect on the ways North Korea may take as a consequence of the international forces new configuration. In this sense, some characteristics of the country will be brought. At first, the State ideology will be studied. In the second part, the relationship between North Korea and China, Europe and the United States is analysed. At last, it is concluded that the regime is seeking to renew itself.